Evaluation of the efficiency of financing the healthcare system: foreign aspect - Bekniyazova, D.S.; Nurgaliyeva, A.A.; Mukina, G.S.; Kenzhin, Zh.B.; Bayandina, G.D. (BUKETOV BUSINESS REVIEW, 2024)
Object: evaluation on the example of foreign countries, of efficiency of financing the healthcare system by com paring non-market and market mechanisms of healthcare and financial management of the healthcare system Methods: in process of the research, the scientific methodology was used, suggesting a systematic approach to solving problems, ensuring the unity of qualitative and quantitative methods. In particular, the method of econometric modeling, correlation analysis of data on health care costs and life expectancy was applied. Findings: in the paper the financial models underlying various health systems (using the example of foreign countries) is compared and analyzed, and also based on the method of econometric modeling, the nature of the correlation between increase in private and public health spending and life expectancy is established. Conclusions: according to the results of the econometric research, the authors concluded that the development and implementation of reforms in the health care system should be based on significant shift in the balance of private and public financing towards the latter. The increase in the degree of participation of private financing in healthcare is justified only by stimulating competition and should not be linked to the reduction in public funding.